Comparison of Lignocaine and Esmolol in attenuating cardiovascular response to laryngoscopy and endotracheal intubation - Shrestha, Anil; Acharya, Subhash Prasad; Amatya, Roshna (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: Laryngoscopy and tracheal intubation induces cardiovascular stress response characterized by tachycardia and hypertension, which are well tolerated in normotensive individuals but are of greater significance in patients with cardiovascular and cerebrovascular disorders. The quest for an effective suppression of these responses continues. Materials and Methods: A randomized, prospective, double blind, placebo controlled study was conducted in which the efficacy of Lignocaine 1.5 mg/kg and Esmolol 1.5 mg/kg were compared in attenuating the cardiovascular response to laryngoscopy and tracheal intubation in sixty patients undergoing elective surgery under general endotracheal anaesthesia. Patients were divided into three groups receiving Lignocaine, Esmolol or Normal saline (control). Anaesthesia was induced with intravenous Thiopental Sodium 5 mg/kg and intubation was facilitated with Vecuronium 0.12 mg/kg after administering the study drug. Blood pressure and heart rate were compared among the three groups. Results: The increase in Systolic blood pressure was not significant, but Diastolic and Mean Arterial Pressures increased significantly in control group whereas it was attenuated more effectively in Esmolol group (p<0.05) compared to lignocaine group. The increase in HR was significantly lower (p<0.05) in Esmolol group compared with lignocaine and control group. Conclusion: Esmolol is more effective than lignocaine in attenuating cardiovascular response to laryngoscopy and tracheal intubation Journal of Society of Anesthesiologists 2014 1(1): 29-35